Rekonstruksi Jihad Menuju Peradaban Pengetahuan Masa Otoritas - Muhammad Raushan Kanzul Fikri (4, 2026)
Jihad is an important requirement in Islamic teachings, obligatory for every Muslim, according to their individual abilities and capacities. However, in the development of religious discourse and public perception, the term jihad is often reduced to the meaning of war (qitāl). This narrowing of meaning has given rise to a negative stigma, namely the assumption that jihad is synonymous with violence and uncivilized acts. However, when referring to authoritative sources in Islam, both the Quran and the Hadith, jihad has a much broader and nobler meaning. Jihad encompasses spiritual struggle, patience, self-control, da'wah (preaching), devotion to parents, and a commitment to fighting for good in various aspects of life. One form of jihad emphasized in the Prophet's hadith is the pursuit of knowledge. The Prophet stated that those who go out to seek knowledge are on the path of Allah until they return. The interpretation of jihad as the pursuit and development of knowledge demonstrates that jihad is not merely a physical act, but an intellectual, moral, and spiritual process oriented towards the advancement of oneself and society. If this broad understanding is realized, the stigma that jihad is an uncivilized activity will naturally fall away. In fact, jihad in the form of knowledge has made a significant contribution to the advancement of knowledge and the development of civilization. From this framework of thought, the concept of